To Compare the Outcomes of Neonates Born to Diabetic Mothers who Received Insulin versus Metformin - Naidu, K. Dhanunjay; Rathod, Sachitra (Asian Journal of Clinical Pediatrics and Neonatology, 2021)
Background: Metformin is being increasingly recognized as a viable and cost-effective substitute for insulin in the management of gestational diabetes mellitus (GDM) across various nations. Nevertheless, the effects of administering metformin to mothers on the developmental patterns of fetal, infant, and childhood growth remain uncertain. Aim: To compare the outcomes of neonates born to diabetic mothers who received insulin versus metformin. Materials and Methods: This study included all neonates who were born alive and whose mothers had pre-existing diabetes mellitus (DM) or gestational diabetes mellitus (GDM) during pregnancy and were registered at the institute during the study period. Mothers were categorized into three distinct groups according to the treatment they received for blood sugar regulation. These groups were as follows: group I, which consisted of mothers who were solely on a meal plan; group II, which included mothers who were prescribed Metformin; and group III, which encompassed mothers who were administered insulin. Results: Among the 150 neonates, 85 (56.67%) were males. Term neonates constituted 125 (83.33%) while preterm and post term neonates accounted to 23(15.33%) and 1(1.33%) respectively. The outcomes of neonates born to mothers across different categories of treatment for their blood sugar levels were compared. It was observed that complications like NICU admission, RD, hypoglycemia, hypocalcemia, NNH and congenital anomalies were significantly increased in the category of mothers receiving insulin. Conclusion: No significant correlation was found between the treatment regimens administered to mothers (insulin, metformin, or diet) and neonatal outcomes, with the exception of neonatal hyperbilirubinemia.